THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE (A Study on Hotdoh Culinary Business in Denpasar) - Ni Luh Putu Esa Pratista; Wayan Gede Supartha (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Employee performance is essential to ensure employees are motivated to carry out their duties and achieve targets. Therefore, companies need to consider factors affecting performance, such as job satisfaction and compensation, so employees can improve their performance. This study aims to examine the role of job satisfaction in mediating the effect of compensation on performance. The research was conducted at Hotdoh Pisang Goreng in Denpasar. The study population consisted of 40 employees, using a saturated sampling method. Data collection was carried out through interviews and questionnaires. The analytical technique used was path analysis. The results showed that compensation has a positive and significant effect on performance. Compensation also has a positive and significant effect on job satisfaction. Additionally, job satisfaction has a positive and significant effect on performance. Job satisfaction significantly mediates the effect of compensation on performance. It is recommended that the management of Hotdoh Pisang Goreng improve performance by paying attention to compensation. Employee job satisfaction can be enhanced by providing fair wages to increase their performance.